Tax, Social Justice, and Economic Stability: The Islamic Taxation System of Ibn Khaldun's Thought - Leany, Muhammad Novan (Journal of Philology and Historical Review, 2024)
The history of tax thought has an important role, position, and contribution in the development of Islamic historiography. Unfortunately, historiography about it is still minimal, leaving various issues of interpretation that are unclear, complicated, and problematic. This issue triggered Ibn Khaldun to comment through his work entitled Al-Muqaddimah. However, Ibn Khaldun's thoughts on Islamic taxation in Al-Muqaddimah have not been written analytically. This article aims to provide analysis and explanation related to Ibn Khaldun's thoughts on taxation. This article is written using a literature study approach to Al-Muqaddimah, besides that the author also uses relevant secondary sources. Ibn Khaldun's thought in Al-Muqaddimah is a response to the accusation that taxes in Islam are a punishment for Muslims and non-Muslims. Taxes are not only important in the development system of Muslim countries, but also to provide an understanding for Muslims about the importance of taxation in social justice and economic stability. According to Ibn Khaldun, since the beginning, taxes have been imposed by the Prophet Muhammad SAW and the caliphs to ensure the state development system. In addition, tax enforcement since the Prophet's era was enforced according to the situation of the times. This is related to efforts to provide protection for Muslims and maintain harmony with non-Muslims.